The medieval stained glass of West Yorkshire - Sprakes, Brian (Corpus vitrearum Medii Aevi - Great Britain / Summary catalogue, 2023)
"The Medieval Stained Glass of West Yorkshire" is the first complete catalogue of the glass in the county predating the Gothic Revival. It presents important and well-known glazing schemes, such as those at Thornhill (adjudged by some the best and important in any church outside York), Elland, and Normanton, alongside glazing that was previously very little known, such as that at Methley and Ripponden. It offers the first overview of stained glass in the region, drawing on dispersed information to give accounts of lost and excavated glass, and placing the schemes in the contexts of donors, makers, and post-installation histories